ASME 1997 Turbo Asia Conference 1997
DOI: 10.1115/97-aa-048
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Heat Transfer and Pressure Drop of Refrigerant R134a in a Plate Heat Exchanger

Abstract: The characteristics of evaporation heat transfer and pressure drop for refrigerant R134a flowing in a plate heat exchanger were investigated experimentally in this study. Two vertical counter flow channels were formed in the exchanger by three plates of commercialized geometry with a corrugated sine shape of a chevron angle of 60°. Upflow boiling of refrigerant R134a in one channel receives heat from the hot downflow of water in the other channel. The effects of the heat flux, mass flux, quality and pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 5 publications
5
51
2
Order By: Relevance
“…However, even the best predictions showed a mean absolute error (MAE) of 40% against the large experimental database, and predicted less than half of the measured data to within a deviation of ±30%. It was also noted in [1] that most of the existing minichannel and microchannel heat transfer correlations were developed based on small data sets [13][14][15][16][17][18][19][20]. As a result, these correlations usually performed well in the parameter range over which they were fit, but did not extrapolate well beyond their often narrow operating range [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even the best predictions showed a mean absolute error (MAE) of 40% against the large experimental database, and predicted less than half of the measured data to within a deviation of ±30%. It was also noted in [1] that most of the existing minichannel and microchannel heat transfer correlations were developed based on small data sets [13][14][15][16][17][18][19][20]. As a result, these correlations usually performed well in the parameter range over which they were fit, but did not extrapolate well beyond their often narrow operating range [1].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of well-characterized experiments with small channels have been published [13,14,16,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. These studies cover a wide range of operating parameters, fluids and physical dimensions, and present a good database against which to validate existing correlations and to support the formulation of new correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Three flow regimes were observed: isolated bubble flow, which is similar to bubbly flow in a large channel; confined bubble flow, which involves an elongated bubble; and annular-slug flow. The heat transfer coefficient for the evaporation of R134a flowing in a small circular copper tube with an inner diameter of 2 mm was measured (Yan & Lin, 1998). It was showed that the evaporation heat transfer coefficient averaged over the entire vapor quality range was about 30-80% higher than that for a large pipe with an inner diameter of 8.0 mm.…”
Section: Introductionmentioning
confidence: 99%
“…(Mishima & Hibiki, 1996;Mishima et al, 1993;Tran et al, 2000;Yu et al, 2002; Table 2. Summary of previous studies on flow boiling heat transfer in mini/microchannels (Lazarek & Black, 1982;Tran et al, 1996;Kew & Cornwell, 1997;Yan & Lin, 1998;Warrier et al, 2002;Yu et al, 2002; 2. Experimental setup and procedure…”
Section: Introductionmentioning
confidence: 99%
“…In the model with equal inner and outer tube length, airflow collided with surface of other tubes, thus exhaust resistance increased. The ratio of total heat transfer coefficient K and pressure drop △P was defined as integrative index to compare characteristics of different models [12]. Fig.…”
Section: Tab1 Different Structures Of Wcb Modelsmentioning
confidence: 99%